Evolution of Spiders and Silk Spinning: Mini Review of the Morphology, Evolution, and Development of Spiders’ Spinnerets - Mariano-Martins, Pedro; Lo-Man-Hung, Nancy; Torres, Tatiana Teixeira (Frontiers in Ecology and Evolution, 2020)
Spiders spinning skills have fascinated mankind since ancient times. These animals owe this ability to unique appendages named spinnerets. These structures are connected to silk-producing glands and are responsible for silk extrusion and manipulation, granting spiders the ability to use the threads for functions far beyond web-building. In spite of the relevance of spinnerets, there is scarce knowledge about their development and evolution. Most research on these structures focused on their morphological aspects, or possible applications of the silk for human purposes. In this mini review, we included this literature, but our main purpose is to introduce and discuss the preeminent hypotheses on the origins of spinnerets in light of an evo-devo perspective. We present the available information on genetic pathways involved in spinneret genesis during spider’s embryonic development, evidencing the eminent need for further research in the evolution and development of spinnerets.